Sistem Buku Tamu Pernikahan Berbasis Web - Stella Nathania (Jurnal Indonesia Sosial Teknologi, 2022)
The registration of guests who attend weddings often encounters a number of problems. Starting from a crowded queue at certain hours or invited guests whose writings are difficult to read. Physical books to record wedding guests can only be kept by one party. These problems can certainly be overcome by designing a Web-Based Wedding Guest Book System Design. Web-Based Wedding Guest Book System is designed with MySQL database system and uses PHP programming language. Guests can choose to enter personal information including name and origin, or ask the reception staff to enter data. Guests are also given the option to enter a short message for the bride and groom. Attendees can also find out about the social media of wedding organizer, hair and makeup artist, dress and suit provider, and decoration provider who work together on bridal weddings on the “about” page of the system. All guest data in attendance can be accessed via the web, so that not only one party can store guest data.